ANALISIS PROGRAM DAN KEGIATAN RESPONSIF GENDER PADA DINAS KESEHATAN KOTA PAREPARE - Rusiah, Andi; Hamdanah, Hamdanah; Nurhamdah, Nurhamdah; Nanning, Nanning (LPPM IAIN Parepare, 2018)
This study aims to analyze gender responsive programs and activities in the City Health Office of Parepare whose results are used as reference for the institution to reformulate policies that describe gender equality and justice so that development outcomes are on target and can provide positive benefits and impacts for both men and women. The formulation of the program and activities compiled consisted of 12 program items which were transcribed in 111 activities. The Twelve Health Service programs deliver the City of Parepare to a better Human Development Index. The program is based on gender-neutral regional technical guidelines. However, there are several programs included in gender specific categories such as the Maternal and Child Health program. Gender responsive programs and activities are still gradual, given that budgeting is still new. Disaggregated data has not been provided on each activity item so that it is difficult to carry out gender analysis, so efforts to find gender gaps are also difficult.